Exploring the Relationship Between Substance Use and Allostatic Load in a Treatment/Research Cohort and in a US Probability Sample (NHANES 2009–2016) - Rogers, Jeffrey M.; Epstein, David H.; Phillips, Karran; Strickland, Justin C.; Preston, Kenzie L. (Frontiers in Psychiatry, 2021)
Allostatic load, an operationalization for cumulative strain on physiology from adaptation (allostasis) to stress over a lifetime, can manifest as damage to cardiovascular, neuroendocrine, and metabolic systems. The concept of allostatic load may be particularly useful in research on substance-use disorders (SUDs), because SUD researchers have sought to better understand the relationship between chronic stressors and drug use. Theoretical models hold that SUDs can be conceptualized as a spiral toward a state of persistent allostasis (i.e., allostasis so persistent as to represent homeostasis at a new, unhealthy setpoint). Regardless of the extent to which those models are accurate, increased allostatic load could be a mechanism by which frequent drug administration increases risk for adverse outcomes. We conducted two secondary analyses to evaluate allostatic load in the context of drug use, including alcohol use, in a locally recruited sample with a high proportion of illicit substance use (N = 752) and in a nationally representative sample from the NHANES 2009-2016. We hypothesized that after controlling for age and other potential confounds, people with longer histories of drug use would have higher allostatic-load scores. Multiple regression was used to predict allostatic load from participants’ drug-use histories while controlling for known confounds. In the locally recruited sample, we found that longer lifetime use of cocaine or opioids was related to increased allostatic load. In NHANES 2009-2016, we found few or no such associations. Lengthy histories of problematic nonmedical substance use may facilitate more rapid increases in allostatic load than ageing alone, and, together with findings from previous investigations, this finding suggests increased risk for chronic disease.